DINAMIKA PERANAN SEKTOR PERTANIAN DALAM PEMBANGUNAN EKONOMI DI KAWASAN SOLO RAYA - Wiwit Rahayu; Nuning Setyowati (Universitas Sebelas Maret, 2016)
This study aims to determine the dynamics of agriculture role in economic development in the region of Solo Raya seen from agricultural sector contribution to the PDRB, the agricultural sector is base sector or not based on the Location Quotien (LQ) analysis, as well as the agricultural sector classification based Klassen Typology analysis. The data used is PDRB of Regency and City in Solo Raya Region and PDRB of Central Java in 2010-2014 based on constant prices of 2010. The results showed that during the 2010-2014 agricultural sector contribution to the PDRB of Regency / City in Solo Raya Region tends to decrease. Contribution of agriculture to the PDRB is highest in Wonogiri regency is 35.01% and the lowest was in Surakarta, namely 0.52%. LQ analysis results indicate that the agricultural sector is base sector in Sragen, Wonogiri, and Boyolali and in Sukoharjo, Karanganyar, Klaten and Surakarta is not base sector. Based on the analysis Typology Klassen, the agricultural sector in Sragen, Sukoharjo, Boyolali, Wonogiri, Karanganyar, and Klaten, categorized as a potential sector, while in Surakarta categorized as a growing sector.